Organizational loyalty and its relation to organizational citizenship - Aoune, Ali; Serraya, El Hadi (Journal of Human Sciences, 2021)
In this study, we discussed the type of relationship between organizational loyalty and organizational citizenship among a sample of employees in the municipality of Tamsin -Touggourt - according to an intermediate variable (gender), and the descriptive, associative approach was adopted, and the sample of this study consisted of (70) workers and workers in the municipality, Two tools were used for the study, the first to measure the level of organizational loyalty prepared by the two researchers, and the second was the measure of organizational citizenship for the researcher "Lee & Allens" (2002), and the study was applied to an exploratory sample to ensure the validity and consistency of the study tools and a basic sample for extracting results, using the statistical program (Spss) The results came As follows: 1-There is a statistically significant correlation between organizational loyalty and organizational citizenship among municipal employees. 2-The absence of statistically significant differences in the level of organizational loyalty among the municipal employees due to the gender variable (male – female). 3- The absence of statistically significant differences in the level of organizational citizenship of the municipality employees due to the gender variable (male - female).